Fluidity of water confined down to subnanometer films. - Raviv, U; Perkin, S; Laurat, P; Klein, J (2004)
A surface force balance with extremely high sensitivity and resolution for measuring shear forces across thin films has been used to investigate directly the dynamic properties of salt-free water (so-called conductivity water) in a gap between two atomically smooth solid surfaces. Our results reveal that no shear stress can be sustained by water (within our resolution and shear rates) down to films of thickness D = D0 = 0.0 +/- 0.3 nm. At short range (D < 3.5 +/- 1 nm), an attractive van der Waals (vdW) force between the surfaces causes a jump into a flat adhesive contact at D0, at which the surfaces rigidly couple. Analysis of the jump behavior reveals that the viscosity of water remains within a factor of 3 or so of its bulk value down to D0. This contrasts sharply with the case of confined nonassociating liquids, whose effective viscosity increases by many orders of magnitude at film thicknesses lower than about five to eight monolayers. We attribute this to the fundamentally different mechanisms of solidification of organic liquids and of water. In the former case, the density increase induced in the films by the confinement promotes solidification, while, in the case of water, such densification (due to vdW attraction between the liquid molecules and the confining walls), in agreement with bulk behavior, suppresses the tendency of the water to solidify.